Content-based image retrieval system using fuzzy colour and local binary pattern with apache lucene - Zulkurnain, Nurul Fariza; Azhar, Mohamad Asyraaf; Mallik, Moksud Alam (Springer, 2022)
The technique of searching for and obtaining related images in image databases is known as image retrieval [1]. It is usually divided into two categories: text-based image recovery (TBIR) and content-based image recovery (CBIR) [2]. A new categorization, semantic-based picture recovery (SBIR), has been added by a few experts. SBIR is used to break down any barriers between low-level provisions and the extraction of substantial-level items. The picture recovery in TBIR is based on literary suggestions and does not examine the original image. The data can be in the form of manual comments or logical clues. Content-based picture recovery (CBIR), then again, permits the client to include an inquiry picture rather than text during the looking through measure. There are four main procedures to build a complete CBIR system which are (1) define image descriptor, (2) index feature vectors, (3)define similarity metric, and (4) searching process.